Sociology Textbook Based on Inside Out Circle Model to Implement Merdeka Belajar-Kampus Merdeka Program - Arfenti Amir; Akhiruddin (Universitas Pendidikan Ganesha, 2023)
Students have a role in maintaining values for the development of country. One effort to strengthen the role of these students is through the independent learning program (MBKM). Independent Learning – Independent Campus (MBKM) is one of the policies of the Ministry of Education, Culture, Research and Technology. This study aims to develop a Sociology textbook based on the IOC (Inside Outside Circle) model for the implementation of MBKM. This research method uses research and development (R & D) which aims to develop certain products and test the effectiveness of these products. The essence of this development research is the validation and revision of the class X sociology textbook based on the 4-D model which consists of 4 stages of development, namely Define, Design, Develop and Desiminate. The results of trials conducted on 35 students showed that student learning outcomes were in the very good category, student learning outcomes were in the good category. Of the 35 students who have completed, individually in the sociology class, it means that students have achieved the KKM that has been set, namely 80%. It can be concluded that students have met the criteria set in the development of sociology textbooks in sociology subjects.